Institutional Setting Enhancement sebagai Solusi Peningkatan Active Learning Mahasiswa untuk Bentuk Pembelajaran Presentasi Kelas - An’im Kafabih (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
This community service aims to enhance the implementation of active learning among university students through an institutional setting enhancement approach in classroom learning. The method used is Participatory Action Research (PAR), where students actively participate as partners in implementing changes through the introduction of structured classroom rules designed to encourage active engagement. The activity was conducted in the Project Evaluation and Islamic Business course at the Faculty of Economics and Business, Universitas Diponegoro, over eight weeks. Several issues were identified, including low student participation, presenters merely reading slides, and the use of smartphones to answer questions without adequate understanding of the material. To address these issues, a set of improved classroom rules was implemented to promote deeper engagement in presentations and discussions. The results indicate that the enhanced institutional setting significantly improved classroom interaction, presentation quality, and student participation during question-and-answer sessions. Statistical analysis using a one-way ANOVA test revealed a significant difference between the average active learning scores before and after the rule enhancement, with a p-value of 0.0042. These findings demonstrate that institutional setting enhancement effectively increases student engagement and improves academic performance